2009
DOI: 10.1002/mawe.200900459
|View full text |Cite
|
Sign up to set email alerts
|

Identification of process parameters affecting distortion of disks for gear manufacture Part I: casting, forming and machining

Abstract: Towards determining the influence parameters on the distortion of gear wheels made from the steel grade 20MnCr5 (SAE 5120), in this work the analysis of the distortion of disks is presented. The parameter identification was performed by means of the design of experiments (DoE). According to a comprehensive approach to distortion engineering, the entire manufacturing chain was considered from casting to the final heat treatment. Due to the complexity of this manufacturing chain the investigation was divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 8 publications
(4 reference statements)
0
26
0
1
Order By: Relevance
“…Both approaches led to a reduced scatter of the change of dishing as well (for more details [4]. However the influences of the material properties and other processes of the manufacturing chain are being analyzed and have been presented elsewhere [2,6].…”
Section: Materials Flow and Distortion Of The Gear Wheel Blanksmentioning
confidence: 99%
See 1 more Smart Citation
“…Both approaches led to a reduced scatter of the change of dishing as well (for more details [4]. However the influences of the material properties and other processes of the manufacturing chain are being analyzed and have been presented elsewhere [2,6].…”
Section: Materials Flow and Distortion Of The Gear Wheel Blanksmentioning
confidence: 99%
“…By analysing the distortion behaviour of disks for the manufacture of gears, Clausen et al [2] identified several process parameters as highly significant regarding shape changes. On basis of a design of experiment (DoE), measurement data of the disks faces, their center hole and circumferences were analysed by means of Fourier series.…”
Section: Introductionmentioning
confidence: 99%
“…The distortion is not only restricted to the teeth. Also, the gear's base body can distort during the manufacturing process [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it was decided to make the samples in the form of rings with a through hole. The formation of distortion is a very complex problem, so the generalization of the problem will only be possible using models with simple geometry [3][4]. Figure 1 shows the geometry of ring prototypes for distortion testing.…”
Section: Geometry Selection For Distortion Testingmentioning
confidence: 99%
“…The use of a particular element will determine the conditions of the carried thermal processes [1][2][3].…”
Section: Introductionmentioning
confidence: 99%